Olfactory Stimulation with Japanese Soy Sauce Improves Upper Limb Performance - Yutaka Yano; Yoshihiro Murata; Mutsuo Taniguchi; Fumino Okutani; Masahiro Yamaguchi; Hideto Kaba (Occupational Therapy International)
Background. We have observed changes in body reactions during cooking, which is one of the treatment modalities used in occupational therapy. The perception of food-related odors during cooking may have behavioral effects on human activities through the activation of appetitive motivation. Objectives. We investigated whether odor components contained in seasonings could facilitate the human motor system and the specificity of this effect. Methods. The subjects were 72 healthy adults, randomly assigned to a water exposure group, a phenylethyl alcohol (PEA, pleasant rose-like odor) exposure group, and a Japanese soy sauce (Koikuchi Shoyu) exposure group (n=24 each). The subjects’ olfactory sense was stimulated by their sniffing of three different test tubes containing 5 ml of water, PEA, or Japanese soy sauce for 20 sec while they were seated. The modified Functional Reach Test (mFRT), which mimics a functional activity that is required in daily living and assesses a reliable measure of sitting balance, was performed prior to and immediately after the sniffing. Results. Sniffing the soy sauce increased the subjects’ mFRT scores. This facilitation effect was odorant-specific and was absent when the subjects were presented with water or PEA. Conclusions. Cooking interventions are aimed at improving tool-handling skills such as using knives and chopsticks. The results indicate that treatment interventions using odors of seasonings would be effective for improving subjects’ physical functions.